First report on association of Meloidogyne graminicola in twister disease of onion: an emerging problem in coastal tract of India - GURUDATTH HEGDE, S. LINGARAJU; A. SRINIVASARAGHAVAN*, SURESH PATIL, V.B. NARGUND (Indian Phytopathology, 2017)
Onion crop grown in west coast of sothern India has been seriously affected by the problem of onion twister disease charetorized by the symptoms viz., twisting of leaf and neck, slight to prominent galls in roots with root proliferation and scanty discolored root system. A survey carried out during rabi/summer of 2011-12 and 2012-13 revealed the prevalence of such disease in all the major onion cultivating areas of Karnataka (India). The highest disease index of 24.05 and 29.37 per cent was noticed Uttar Kannada district during 2011-12 and 2012-13 respectively. Aetiological investigations revealed the association of a nematode with symptomatic onion plants having root galls. Nematode when inoculated, resulted in slender plants with typical abnormal elongation of leaf with proliferation and neck twisting during initial stage and at later stage whole plant appeared to be abnormal showing typical twisting symptoms. Artificially inoculated plant with typical symptoms were found to have severe galling with typical hooks like roots. At later stage discoloration and complete destruction of root system demonstrated the Koch’s postulate for the involvement of isolated nematode in the disease. Identity of the nematode was confirmed as Meloidogyne graminicola by morphometric and perineal pattern studies. This is the first report of association of rice root knot nematode involved in onion twister disease.